Penilaian Kualitas Visual sebagai Dasar Pengembangan Perancangan Lanskap Objek Wisata Desa Budaya Kertalangu, Bali - Putu Nala Viswa Dharma; Hinijati Widjadja; Qurrotu’Aini Besila (http://arl.faperta.ipb.ac.id/, 2021)
Bali is a tourist destination that is very popular in the country of Indonesia with a wealth of natural and cultural potential that is presented on this island of a thousand temples. One of the tourist objects in Bali, especially in Denpasar City, is the Kertalangu Cultural Village Tourism Object, which is located in the village of Kesiman Kertalangu. This tourism object offers local cultural potential and visual potential in the form of rice fields which can be an alternative tourism in the middle of conventional tourism development in Denpasar. However, the lack of attractiveness in this tourist attraction area has made visitors less enthusiastic about coming on a tour, so research is needed regarding the assessment of visual quality in this area as an effort to increase the attractiveness of traveling by optimizing the visual quality of the site. The purpose of this study was to examine the visual quality that can be an attraction in the Kertalangu Cultural Village. The methods used are VRAP and field surveys. The results provide some recommendations to develop landscape designs for Kertalangu Cultural Village based on the use of visuals and local cultural values.